PENDUGAAN UMUR SIMPAN MAKANAN TRADISIONAL BERBAHAN DASAR BERAS DENGAN METODE ACCELERATED SHELF-LIFE TESTING (ASLT) MELALUI PENDEKATAN ARRHENIUS DAN KADAR AIR KRITIS - Vivi Nuraini; Yannie Asrie Widanti (JURNAL AGROTEKNOLOGI, 2020)
The expired date is important information that consumers should know. However, many traditional foods have not written an expiration due date. The purpose of this study was to estimate the shelf life of two (2) types of traditional rice-based foods intip and kembang goyang. Estimation of shelf life was carried out using the Accelerated Shelf-life Testing (ASLT) method using the Arrhenius approach and the critical moisture content approach. The calculation of shelf life in the Arrhenius approach to kembang goyang has been obtained respectively 0.45 months, 0.50 months, and 0.47 months at respective temperatures (25oC, 35oC and 45oC). The results of shelf life kembang goyang through the water content approach obtained 0.43 months at 75% RH. The results of the arrhenius approach to intip showed that shelf life of 0.37 months, 0.45 months, and 0.53 months at each temperature (25oC, 35oC, and 45oC). The critical water content approach for intip has obtained a shelf life of 0.58 months (RH 75%). Intip has a slightly larger shelf life when analyzed using the critical moisture content method. Keywords: ASLT, intip, kembang goyang, shelf life